2016
DOI: 10.2174/0929866523666160511151320
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Antimicrobial Peptides from Spiders and Scorpions

Abstract: The venoms of spiders and scorpions contain a variety of chemical compounds. Antimicrobial peptides (AMPs) from these organisms were first discovered in the 1990s. As of May 2015, there were 42 spider’s and 63 scorpion’s AMPs in the Antimicrobial Peptide Database (http://aps.unmc.edu/AP). These peptides have demonstrated broad or narrow-spectrum activities against bacteria, fungi, viruses, and parasites. In addition, they can be toxic to cancer cells, insects and erythrocytes. To provide insight into such an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 122 publications
(214 reference statements)
0
41
0
Order By: Relevance
“…Pore formation and membrane disruption were also reported in human bladder cancer cells treated with magainin II and cecropin B AMPs (Lehmann et al 2006;Suttmann et al 2008). It has previously been suggested that AMPs might be effective anti-cancer agents (Wang and Wang 2016;Crusca et al 2018), due to surface membrane charge differences. The outer plasma membrane leaflet in normal cells exhibits an overall neutral charge as its main components are the zwitterionic phospholipids, phosphatidylcholine and sphingomyelin (Dolis et al 1997;Hoskin and Ramamoorthy, 2008;Riedl et al 2014).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Pore formation and membrane disruption were also reported in human bladder cancer cells treated with magainin II and cecropin B AMPs (Lehmann et al 2006;Suttmann et al 2008). It has previously been suggested that AMPs might be effective anti-cancer agents (Wang and Wang 2016;Crusca et al 2018), due to surface membrane charge differences. The outer plasma membrane leaflet in normal cells exhibits an overall neutral charge as its main components are the zwitterionic phospholipids, phosphatidylcholine and sphingomyelin (Dolis et al 1997;Hoskin and Ramamoorthy, 2008;Riedl et al 2014).…”
Section: Discussionmentioning
confidence: 73%
“…The appearance of phosphatidylserine on the outer membrane leaflet regulates malignant transformation by primarily suppressing anti-tumour immune responses (Utsugi et al 1991). These observations have led to many suggestions that AMPs might be effective anti-cancer agents (Wang and Wang 2016;Crusca et al 2018), providing that there is a sufficient distinction (effective therapeutic index) between cytolytic effects on tumour and non-tumour cell membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extra‐intestinal digestion of spiders may impose very strong selection on microbial populations, probably leading to a significant drop in population sizes before they enter the spider's gut. Spider venom, for example, is known to contain antimicrobial peptides, which kill microbes before ingestion (Wang & Wang, ; Yan & Adams, ). Such reduced population sizes may not cause a significant increase in gut microbial load.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lethal toxins found in these venoms are, in fact, peptides able to block or modulate ion channels in a myriad of cell surfaces (Pineda et al 2014). Since the role of many different ion channels in cancer pathophysiology has become evident, ion channel toxins from spiders and scorpions have been proposed to be used as anticancer peptides (Bubien et al 2004;Wang and Wang 2016;Nicoletti et al 2017), as molecular probes to elucidate the functional aspects of these channels in cancer progression and migration (Rooj et al 2012;Aissaoui et al 2018) or chemically engineered to be used as tumor imaging agent in both diagnoses and prognoses (Aroui et al 2015;Moore et al 2013;Cohen-Inbar and Zaaroor 2016). New drugs aiming at overcoming resistance through the activation of other mechanisms of cell death, like necroptosis, are currently being investigated.…”
Section: Introductionmentioning
confidence: 99%